Pertanggungjawaban Pidana terhadap Pencemaran Lingkungan di Indonesia - I Komang Agus Edi Suryawan; I Nyoman Gede Sugiartha; I Nyoman Sutama (Jurnal Interpretasi Hukum, 2021)
The environment as a place to live and at the same time as a storage for waste from human activities. Can return to normal if the waste does not damage the environment. Environmental pollution has a bad impact on society. Research and reports from related institutions noted Indonesia's environmental problems, namely polluted rivers, the quality of the water must be considered because it is widely used by the community. The research method in this writing uses normative legal research, first examining the problem using the basis of statutory law. Discussion of issues regarding legal arrangements for criminal acts of environmental pollution and responsibility for criminal acts of environmental pollution according to criminal law in Indonesia. In this case, the legal provisions for criminal acts of environmental pollution are regulated in Law No.32 of 2009 concerning Environmental Protection and Management. The accountability may be imposed on individuals, corporations and authorized officials.